Surgical Outcome of Moyamoya Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
Researchers at Seoul National University Children's Hospital, Korea, analyzed the clinical characteristics and prognostic factors for outcome of 410 pediatric cases of moyamoya disease (MMD) after bypass surgery.